2017
DOI: 10.1016/j.compchemeng.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A superstructure-based framework for bio-separation network synthesis

Abstract: Modern biotechnologies enable the production of chemicals using engineered microorganisms. However, the cost of downstream recovery and purification steps is high, which means that the feasibility of bio-based chemicals production depends heavily on the synthesis of cost-effective separation networks. To this end, we develop a superstructure-based framework for bio-separation network synthesis. Based on general separation principles and insights obtained from industrial processes for specific products, we firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…Previous studies have shown that the separation costs, and especially capital costs, increases harply with lower titer. [30][31][32][33][34][35] Thus, to keep the capital investment for the envisioned biorefinery low (2000Mgday À1 ), it is crucial to structure the downstream processes to funnel the complex mixturet op roducts that can be isolatede conomically. [26,[36][37][38][39][40][41][42] An alternative approachi st oe ngineer bioenergy feedstocks to produce high levels of as ingle hydroxycinnamate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the separation costs, and especially capital costs, increases harply with lower titer. [30][31][32][33][34][35] Thus, to keep the capital investment for the envisioned biorefinery low (2000Mgday À1 ), it is crucial to structure the downstream processes to funnel the complex mixturet op roducts that can be isolatede conomically. [26,[36][37][38][39][40][41][42] An alternative approachi st oe ngineer bioenergy feedstocks to produce high levels of as ingle hydroxycinnamate.…”
Section: Introductionmentioning
confidence: 99%
“…In an industrial-scale biorefinery,p otential processes that could be used to isolate pCA and FA include distillation, membrane separation, adsorption, and extraction. [35,51,52] pCA and FA are (hot-)water-soluble, nonvolatile chemicals;d istillation of the water of the APL would, therefore, yield ac oncentrated mixture of pCA, FA,a nd waxes/oligomers.T he distillation of pCA and FA to pure products is not viable as they decarboxylate thermally to form 4-vinylphenol and 4-vinylguaiacol. [53] Furthermore, the distillation of an APL would require the evaporation of al arge portion of water,w hich would increasee nergy costs significantly.A lternatively,m embranesc an be used to separate pCA and FA as permeates or to concentrate them by the dehydration of the APL.…”
Section: Introductionmentioning
confidence: 99%
“…A scheme incorporates a list of technologies available for a set of tasks, while a superstructure incorporates a number of alternative specific technologies and relevant interconnections. Superstructure optimization has been proposed for the synthesis of separation networks [20,[38][39][40][41][42] as well as the development of bio-processes [33,39,[43][44][45][46][47][48][49]. However, these studies were mostly focused on either general methodological discussions or analysis for specific products on a case-by-case basis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the appropriate selection of superstructure representation method is critical. There are many representations such as state-task-network [20,21], state-equipment-network [21], P-graph [22,23], state-space [24,25] , HEN and MEN building blocks [26,27], phenomena building blocks [28][29][30], process-group contribution method [31], and unit-port-conditioning-stream (UPCS) approach [32,33]. We recently proposed a new superstructure representation method using building blocks for systematic process intensification [34][35][36].…”
Section: Introductionmentioning
confidence: 99%